Gloss to the judgment of the District Court in Łęczyca of June 1, 2017 (II K 201/16) [on the justified fear of flight or hiding and the use of direct coercion for the purpose of detention] - Prusek, Michał (The Opole Studies in Administration and Law, 2023)
The fear of fleeing and hiding has been the basis of proper detention for several decades. Nevertheless, it is not interpreted uniformly. The fulfillment of the commented base raises doubts if a person moves away from his own driveway towards the house, closes himself in the house and moves inside it, avoiding contact with the policemen. Moreover, the jurisprudence ignores the problem of the insufficient basis for the application of direct coercion for the purposes of conducting a trial detention.